Review of TFEB-amplified renal cell carcinoma with focus on clinical and pathobiological aspects - Naoto Kuroda; Emiko Sugawara; Chisato Ohe; Fumiyoshi Kojima; Riuko Ohashi; Shuji Mikami; Yoji Nagashima; Kvetoslava Peckova; Michal Michal; Ondrej Hes (Polish Journal of Pathology, 2022)
The disease entity of TFEB-amplified renal cell carcinoma (RCC) has been recently established. In this article, we review such cases. Clinically, the age of patients ranged from 28 to 83 years with a mean age of 62.8 years. The size of the tumor ranged from 1.9 to 19.5 cm with a mean size of 8.7 cm. The tumor demonstrated a variety of architectural patterns such as solid, alveolar, papillary, pseudopapillary, nested or tubular. The International Society of Urological Pathology (ISUP) grade usually corresponds to grade 3 or 4. Cytomorphology shows eosinophilic, clear, amphophilic or even oncocytic cytoplasm. Necrosis can be frequently observed. Neoplastic cells with TFEB-amplified RCC show diffuse or patchy positivity for TFEB. Fluorescence in situ hybridization frequently show the amplification of more than 10 or 20 copies of the TFEB gene. Most TFEB-amplified RCCs behave in an aggressive fashion. Metastasis frequently occurs. In conclusion, this tumor seems to be characterized by occurrence in older patients, frequent necrosis, papillary/pseudopapillary growth pattern, high-grade nuclear grade, TFEB gene amplification, and aggressive clinical behavior. In order to clarify whether this tumor is a distinct entity from previously described renal tumors or not, a further examination in a large scale study will be required in the future.